O12-2 The relationship between socio-economic group and work-related mental ill-health. (1st September 2016) - Hussey, Louise; Money, Annemarie; Gittins, Matthew; Agius, Raymond
Abstract : Introduction: Inequalities in health have long been described showing an inverse relationship between social class and morbidity. However, analysis of work-related mental ill-health (WRMIH) and socio-economic group reported by General Practitioners (GPs) show incidence rates are greater amongst higher socio-economic groups. The Health & Occupation Research network (THOR) collects data on WRMIH from GPs and occupational physicians (OPs); and (until 2009) from consultant psychiatrists. This study aimed to analyse the psychosocial factors associated with the medically reported incidence of WRMIH in different socio-economic groups. Methods: With each case of WRMIH, participating physicians reported the associated occupation and psychological stressor. Occupations were coded using the National Statistics Socio-Economic Classification (NS-SEC). A multi-level logistic regression (adjusted by age and gender) calculated odds ratios (ORs) reporting the likelihood of the stressor occurring within each socio-economic group compared to the highest group – 'Large employers & higher managerial occupations' (as reference category). Results: Results from all three types of reporting physicians similarly showed how socio-economic groups were exposed to significantly different workplace psychological stressors. Cases reported from the highest socio-economic group were more likely to be associated with workload and workplace change with a fall in ORs with decreased socio-economic status, e.g. for workload, ORs in the lowest NS-SEC group were 0.51 (GPs), 0.14 (OPs) and 0.16 (psychiatrists). However, workers within the lower NS-SEC groups were more likely to have problems associated bullying/interpersonal difficulties, e.g. for bullying, ORs in the lowest NS-SEC group were 2.60 (GPs), 1.76 (OPs) and 1.60 (psychiatrists). Conclusions: WRMIH rates may be greatest amongst the highest socio-economic groups as they are more likely to have problems associated with a heavy workload and workplace change such staff shortages and organisational restructure. Information from this study may help develop workplace interventions targeted to prevent psychosocial factors affecting different sections of the workforce.